2019
DOI: 10.3382/ps/pey551
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and evolution of infectious bursal disease virus circulating in Turkish broiler flocks

Abstract: The emergence of new infectious bursal disease virus ( IBDV ) variants can threaten poultry health and production all over the world causing significant economic losses. Therefore, this study was performed to determine IBDV molecular epidemilogy, VP2 gene variation, and corresponding pathological lesions in IBDV infected chickens in Turkey. For this, 1855 bursa of Fabricius samples were collected from 371 vaccinated broiler flocks. Atrophia and haemorrhages were seen in the bursa Fabrici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Regarding the dIBDV strains, three main successive inter-continental migration events were detected: to vvIBDV and 90.5% were vaccine-like cIBDV (Yilmaz et al, 2019). A similar scenario of co-circulation of vvIBDV and vaccine-like strains was reported in more limited studies performed in Iran, Iraq, Pakistan, Egypt, Jordan and Kuwait (Amin & Jackwood, 2014;Khan et al, 2019;Michel & Jackwood, 2017;Norouzian, Farjanikish, & Hosseini, 2017;Samy et al, 2019).…”
Section: Epidemiological History Of the Dibdv Strainssupporting
confidence: 72%
See 1 more Smart Citation
“…Regarding the dIBDV strains, three main successive inter-continental migration events were detected: to vvIBDV and 90.5% were vaccine-like cIBDV (Yilmaz et al, 2019). A similar scenario of co-circulation of vvIBDV and vaccine-like strains was reported in more limited studies performed in Iran, Iraq, Pakistan, Egypt, Jordan and Kuwait (Amin & Jackwood, 2014;Khan et al, 2019;Michel & Jackwood, 2017;Norouzian, Farjanikish, & Hosseini, 2017;Samy et al, 2019).…”
Section: Epidemiological History Of the Dibdv Strainssupporting
confidence: 72%
“…Except for the recent inter‐continental event of introduction from Brazil and Canada, there are no additional records of the dIBDV lineage in Western Asia. An extensive surveillance in Turkey found that 9.5% of the strains corresponded to vvIBDV and 90.5% were vaccine‐like cIBDV (Yilmaz et al, ). A similar scenario of co‐circulation of vvIBDV and vaccine‐like strains was reported in more limited studies performed in Iran, Iraq, Pakistan, Egypt, Jordan and Kuwait (Amin & Jackwood, ; Khan et al, ; Michel & Jackwood, ; Norouzian, Farjanikish, & Hosseini, ; Samy et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These results are due to antigenic drift in inside or outside of hydrophilic region and hydrophobic region of VP2 that leads to some sites to become more stable and others less stable. Also, the mutations of VP2 are responsible for viral antigenicity, pathogenicity, and tissue tropism as reported by (23,28). The VP2-3-4 of segment A of two Iraqi detected strains were closely related to the Chinese strain (under accession number AY628217.1) both with 99% homology and the VP5 of segment A of two Iraqi detected strains were showed a high nucleotide homology to the Chinses strain (under accession number AF692943.1) both with 99%.…”
Section: Phylogenetic Tree Analysismentioning
confidence: 59%
“…Samples were also screened to detect the presence of infectious bronchitis virus (IBV) (25), infectious bursal disease virus (IBDV) (24), avian metapneumovirus (aMPV) (5), and infectious laryngotracheitis (ILTV) (26) as part of routine diagnostic work, as described previously. For all PCR reactions to detect either DNA or viral RNA, posi-tive and negative controls were used.…”
Section: Methodsmentioning
confidence: 99%
“…Many viral and bacterial diseases are of economic significance in the broiler industry worldwide (5,6,22,24). Although the importance of infectious coryza caused by A. paragallinarum and its economic consequences in broiler flocks have previously been discussed in a number of studies (10,18), the available information on many countries, including Turkey, is limited.…”
Section: Detection Of a Paragallinarum And Viral Pathogens By Pcr Rmentioning
confidence: 99%